2,4-Diiodoaniline - Smith, Graham (International Union of Crystallography, 2009)
The structure of the title compound, C(6)H(5)I(2)N, shows a weak intermolecular amine–amine N—H⋯N hydrogen-bonding interaction, giving a helical chain which extends along the a axis. An intramolecular N—H⋯I hydrogen bond is also observed.